Highlights from the OGFIMS-IITA project review meeting - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
The Review Meeting for the Ogun State Farmers Information Management System (OGFIMS) project, funded by the Ogun State Economic Transformation Project (OGSTEP) and supported by the World Bank, brought together the project implementation team and key stakeholders from the Ogun State Government and OGSTEP. The purpose of the meeting was to assess progress, strengthen collaboration, and work towards achieving the project's goals.